Stability of Synthesized Brushite in Physiological Media for the Possible Bone-Regenerative Use - Vilma Delgado-Morales; Lizbeth Barragán-Maldonado; Mercedes Salazar-Hernández; Alfonso Talavera-Lopez; Alba N. A. Ardila; Oscar Joaquín Solis-Marcial; Jose A. Hernández (International Journal of Biomaterials, 2025)
The advancement of science and technology has helped humans solve different problems related to their health. Among these applications are biomaterials, which are materials synthesized by humans for medical or biological use, representing a market and innovation with potential. The best known biomaterials are calcium phosphate cements (CPCs) that are used as bone substitutes, which show a similarity to bone minerals such as apatites such as dicalcium phosphate dihydrate, and it was synthesized and tested in previously prepared simulated intestinal and body fluids to analyze its stability under specific physiological conditions. Purity was determined by the ash method, giving an average of 73% and 85% in the different tests carried out. The characterization study was involved using ATR-FTIR, XRD, SEM, and EDS where changes were observed in the crystalline structure, in the bonds of the functional groups present on the surface and the morphology of Brushite causing the interaction with the different simulated fluids transformation into monetite, amorphous dicalcium phosphate, and hydroxyapatite.